“On an island by myself”: implications for the inclusion of autistic students in self-contained classrooms in public elementary schools - Ahlers, Kaitlyn; Hugh, Maria L.; Tagavi, Daina; Eayrs, Curtis; Hernandez, Alyssa M.; Ho, Theodore; Locke, Jill (Frontiers in Psychiatry, 2023)
Introduction: Autistic students have limited access to inclusive classes and activities in their schools. Principals and special education teachers who directly teach and administer programs for autistic elementary students can offer critical insight into factors, such as educators' attitudes, that may impact inclusive opportunities in schools. These attitudes may serve as barriers to or facilitators of promoting an inclusive school setting.Methods: Semi-structured interviews with 26 elementary school principals and 26 special education teachers explored their experiences implementing evidence-based practices for autistic students (pivotal response training, discrete trial training, and visual schedules) in 26 self-contained classrooms in the United States. Autism-specific culture and inclusion emerged as a theme, which was analyzed for this paper.Results: An inductive approach to thematic analysis revealed principals' and special education teachers' perspectives regarding the "autism-specific culture" in the school, including attitudes towards and inclusion of autistic students in self-contained classrooms in the broader school environment. Analysis of text related to "autism-specific culture" detailed aspects of inclusion, factors (i.e., barriers and facilitators) affecting inclusion, principals' and special education teachers' attitudes towards autistic students placed in self-contained classrooms, attitudes of other school staff towards teachers in self-contained classrooms, and recommendations to support an inclusive school environment for autistic students.Discussion: Results suggest that valuing "equal" access to classes and activities for autistic students in self-contained classrooms may not be sufficient for promoting an inclusive school environment, Educators may benefit from targeted strategies to facilitate inclusion. Strategies range from supporting educators' attitudes and knowledge of autism to shifting physical aspects of the school environment (e.g., location of classrooms). Additional implications for supporting the true inclusion (i.e., inclusion that goes beyond physical inclusion) involves of autistic students in self-contained classrooms schools are discussed.